Removal of Lead (II) By Nitric Acid-Modified Activated Carbon - Loo, Li Yin (2006)
The effect of varying physical and chemical properties of activated carbons on the adsorption of Pb2+ was studied by modifying commercial activated carbon with HNO3. The activated carbon was crushed and sieved into 200-300 m in size and modified with different concentration of nitric acid (3, 6 and 9 M) at different reflux time (6, 12 and 24 hours), and labelled as AXCs. A portion of the AXCs was subjected to calcination process and assigned as HTs. Surface area and porosity of AXCs and HTs were characterized. The decreases in the surface area, micropore area and micropore volume of the AXCs was due to the increasing of the surface oxygen group. The presence of carboxylic groups has been proven from the DTG curve and FTIR spectra. The adsorption experiments were performed to investigate the efficiency of Pb2+ removal at different initial concentrations (25, 50, 75 and 100 ppm) and different temperatures (303, 313, 323 and 333 K) by AXCs and HTs. The results showed that adsorption capacity of the AXCs is higher than that of HTs; the higher the concentration of nitric acid and the longer the refluxing time during the oxidation treatment the higher the percentage removal of the lead ion. The adsorption kinetics and adsorption equilibrium of Pb2+ obeyed the pseudo second-order and Langmuir isotherm model respectively, which indicates that the adsorption of Pb2+ by AXCs might be via chemisorption. The adsorption Pb2+ onto AXCs was found to be thermodynamically, spontaneous and exothermic reaction. The adsorption of Pb2+ in multi component system was also investigated. In the single system, the adsorption affinity of AXC(9)24 to the Pb2+ is greater than Cu2+ and Zn2+. The percentage removal of Pb2+ by AXC(9)24 decreased in the binary and ternary mixture system. The percentage removal of Pb2+ by Cu2+-loaded and Zn2+-loaded AXC(9)12 was lower then AXC(9)12. The competitive adsorption amongst Pb2+, Cu2+ and Zn2+ might be apparent for the multi component system.